Die Vergegenwärtigung höfischer Lustbarkeiten: André Félibiens 'Divertissements de Versailles' (1674/1676) - Steigerwald, Jörn (Im-Materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag)

Die Geburt der italienischen Liebestragödie. Scipione Maffeis 'Merope'. - Steigerwald, Jörn (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Der Zorn des ehrlichen Mannes. Die Neudeutung von Molières 'Misanthrope' in der 'Deutschen Schaubühne - Steigerwald, Jörn (Theater-Transfers. Akkulturationen des europäischen Dramas in Gottscheds 'Deutscher Schaubühne')

ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730). Einleitung. - Steigerwald, Jörn (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Trendbericht Organische Chemie 2022 - Andexer, Jennifer N.; Beifuss, Uwe; Brasholz, Malte; Breinbauer, Rolf; Breugst, Martin; Dumele, Oliver; Ernst, Martin; Ganardi, Ruth; Giese, Michael; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Synthesis of Bifunctional Phosphonium Salts Bearing Perfluorinated Side Chains and Their Application in the Synthesis of Cyclic Carbonates from Epoxides and CO 2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (Asian Journal of Organic Chemistry)
Keywords: Organic Chemistry

Cover Feature: Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives (Chem. Eur. J. 23/2022) - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Cover Picture: Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates (Angew. Chem. Int. Ed. 31/2022) - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Frustrated Lewis Pair‐Catalyzed Hydroboration of Nitriles: FLP Versus Borenium Catalysis - Sieland, Benedikt; Hoppe, Axel; Stepen, Arne J.; Paradies, Jan (Advanced Synthesis & Catalysis)
Keywords: General Chemistry

Was ist und was leistet hermeneutische Ethik? - Schmidt, Jochen (Ethik in der Hermeneutik - Hermeneutik in der Ethik)

Was wir uns schulden: Freiheit und Pflichten gegen sich selbst - Schmidt, Jochen

Mental rotation with colored cube figures - Rahe, Martina; Weigelt, Matthias; Jansen, Petra (Consciousness and Cognition)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology

Stating Comparison Score Uncertainty and Verification Decision Confidence Towards Transparent Face Recognition - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Damer, Naser; Kuijper, Arjan (33nd British Machine Vision Conference 2022)
Keywords: Computer Vision and Pattern Recognition (cs.CV); FOS: Computer and information sciences; FOS: Computer and information sciences

Familienbildung und Ungleichheit: Sozialraumtheoretische Perspektiven auf das (Nicht)Erreichen von Eltern - Landhäußer, Sandra; Faas, Stefan (Familienbildung – Praxisbezogene, empirische und theoretische Perspektiven)
Familienbildung ist ein Arbeitsfeld, auf das sich zunehmend Aufmerksamkeit richtet. Der Diskurs wird intensiver; von Bildungs-, Familien- und Jugendhilfepolitik wird sie als wichtige Akteurin adressiert. Zugleich steht sie vor großen strukturellen, personellen und inhaltlichen Herausforderungen. Das traditionelle Spannungsverhältnis zwischen Erwachsenenbildung und Kinder- und Jugendhilfe erhält neue Brisanz. Der vorliegende Band entfaltet differenzierte Fragestellungen und eröffnet Perspektiven – mit Schwerpunkten auf Politische Familienbildung und Professionalisierung.
Keywords: Familie | Erwachsenenbildung | Jugendhilfe | Markt | Soziale Arbeit

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Strain mode-dependent weighting functions in hyperelasticity accounting for verification, validation, and stability of material parameters - Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Optimized material parameters obtained from parameter identification for verification wrt a certain loading scenario are amenable to two deficiencies: Firstly, they may lack a general validity for different loading scenarios. Secondly, they may be prone to instability, such that a small perturbation of experimental data may ensue a large perturbation for the material parameters. This paper presents a framework for extension of hyperelastic models for rubber-like materials accounting for both deficiencies. To this end, an additive decomposition of the strain energy function is assumed into a sum of weighted strain mode related quantities. We propose a practical guide for model development accounting for the criteria of verification, validation and stability by means of the strain mode-dependent weighting functions and techniques of model reduction. The approach is successfully applied for 13 hyperelastic models with regard to the classical experimental data on vulcanized rubber published by Treloar (Trans Faraday Soc 40:59–70, 1944), showing both excellent fitting capabilties and stable material parameters.
Keywords: Mechanical Engineering

Goal-oriented error estimation and h-adaptive finite elements for hyperelastic micromorphic continua - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Technisches Lernen im Sachunterricht inklusiv gestalten - Fördert ein inklusionssensibles Seminar in der universitären Lehrerbildung das Interesse und die Selbstwirksamkeitserwartung von Bachelorstudierenden? - Schröer, Franz; Tenberge, Claudia (widerstreit Sachunterricht - Auf die Lehrkraft kommt es an? Professionalisierung von Lehrkräften für inklusiven Sachunterricht)

Elementary symmetric polynomials and martingales for Heckman-Opdam processes - Rösler, Margit; Voit, Michael (Contemporary Mathematics)
We consider the generators $L_k$ of Heckman-Opdam diffusion processes in the compact and non-compact case in $N$ dimensions for root systems of type $A$ and $B$, with a multiplicity function of the form $k=κk_0$ with some fixed value $k_0$ and a varying constant $κ\in\,[0,\infty[$. Using elementary symmetric functions, we present polynomials which are simultaneous eigenfunctions of the $L_k$ for all $κ\in\,]0,\infty[$. This leads to martingales associated with the Heckman-Opdam diffusions $ (X_{t,1},\ldots,X_{t,N})_{t\ge0}$. As our results extend to the freezing case $κ=\infty$ with a deterministic limit after some renormalization, we find formulas for the expectations $\mathbb E(\prod_{j=1}^N(y-X_{t,j})),$ $y\in\mathbb C$.

Rapid Explainability for Skill Description Learning - Demir, Caglar; Anna, Himmelhuber; Liu, Yushan; Alexander, Bigerl; Moussallem, Diego; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2022)
Keywords: drill raki dice demir ngonga

Hardware-agnostic computation for large-scale knowledge graph embeddings - Demir, Caglar; Ngomo, Axel-Cyrille Ngonga (Software Impacts)

Arbitrage in the Market for Cryptocurrencies - Crépellière, Tommy; Pelster, Matthias; Zeisberger, Stefan (Journal of Financial Markets)

Die Luftfahrt zwischen Liberalisierung und Konsolidierung - eine wettbewerbspolitische Analyse von Low-Cost- und Networkairlines - Bas, Sahin

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

Energy Efficiency as Key for Climate Neutral Business - Knorr, Lukas; Meschede, Henning

Renewable energies for the efficient operation of a press hardening line - Knorr, Lukas

Physics Textbooks - as an important tool for learning and teaching - Kapanadze, Marika; Jonas-Ahrend, Gabriela; Mazzolini, Alexander; Joubran, Fadeel

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

GDSU-Journal

The importance of primary school teachers’ self-efficacy beliefs and their attitudes for their everyday practices in heterogeneous classrooms. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers’ self-efficacy in inclusive education – An investigation of the associated sources. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

How to explain primary school teachers’ self-efficacy to teach in inclusive classrooms. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

The importance of parental feedback for children’s reading motivation and their reading comprehension. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Hellmich, Frank; Hoya, Fabian Karl

On-Chip Quantum Communication Devices - Trenti, Alessandro; Achleitner, Martin; Prawits, Florian; Schrenk, Bernhard; Conradi, Hauke; Kleinert, Moritz; Incoronato, Alfonso; Zanetto, Francesco; Zappa, Franco; Luch, Ilaria Di; Cirkinoglu, Ozan; Leijtens, Xaveer; et al. (Journal of Lightwave Technology)
Keywords: General Engineering

Lehren und Lernen mit (digitalen) Medien im Pädagogikunterricht - Herzig, Bardo; Martin, A. (Handbuch Pädagogikunterricht)

Medienbildung als Radikalisierungsprävention? - Herzig, Bardo (Radikalisierungsnarrative online. Perspektiven und Lehren aus Wissenschaft und Prävention)

Algorithmische Entscheidungssysteme und digitale Souveränität - Herzig, Bardo; Sarjevski, E.; Hielscher, D. (merz Wissenschaft: Digitalität und Souveränität. Braucht es neue Leitbilder der Medienpädagogik?)

Informal Workplace Learning at a Glance: Validation of Short Measure for White-Collar Workers. - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (European Association of Work and Organizational Psychology Congress 2022.)

Off Your Own Bat or Aided by Others: A Vignette Study on the Role of Metacognitions and Social Support for Informal Workplace Learning. - Decius, Julian; Knappstein, Michael; Seifert, Andreas (Hawaii International Conference On Education.)

Off Your Own Bat or Aided by Others? An Investment-Reward Typology of Metacognition and Social Support at Work. - Seifert, Andreas; Decius, Julian; Knappstein, Michael (EARLI SIG14 Conference)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Digitaler Wechselunterricht in der gymnasialen Oberstufe – ein Modell mit Zukunft? - Rogge, Tim; Seifert, Andreas (AEPF-Tagung „Lehren und Lernen neu gedacht – Konsequenzen für das zukünftige Bildungswesen“)

Pädagogische Kompetenz als Ausgangspunkt beruflichen Könnens!? Ergebnisse der Kompetenzmessung angehender Lehrkräfte unter Berücksichtigung individueller Voraussetzungen. - Caruso, Carina; Seifert, Andreas (Religionspädagogische Beiträge. Journal for Religion in Education.)

Validierung von Testinstrumenten durch Testmotivationsindikatoren. - Watson, Christina; Meier, Jana; Seifert, Andreas; Küth, Simon; Scholl, Daniel (DGPs-Tagung „View on of Science“, Hildesheim)

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? Ergebnisse der Messung pädagogischer Kompetenzen Studierender in Deutschland. - Caruso, Carina; Seifert, Andreas (Österreichisches Religionspädagogisches Forum)

Inclusive math practices in primary school. Twelfth Congress of the European Society for Research in Mathematics Education - Häsel-Weide, Uta; Nührenbörger, M. (Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

(Selbst-)Einschätzungen zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Sachunterrichtsstudierenden an der Universität Paderborn - Brenke, Laurien; Kirsch, Alexander; Blumberg, Eva (GDSU-Journal)

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. 30. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik). Thema: "Nachhaltige Bildung in der Grundschule" - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-service teachers’ team-teaching practices and children’s competence development in inclusive schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

DiPoSa: Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts: Identifizieren, Konzeptualisieren und Implementieren. Vortrag auf der Auftaktveranstaltung zur BMBF-Förderrichtlinie „Förderbezogene Diagnostik in der inklusiven Bildung“ im Rahmen des BMBF-Metavorhabens „Qualifizierung für inklusive Bildung“ - Schroeder, René; Blumberg, Eva; Miller, Susanne; Kottmann, Brigitte; Reh, Anne; Franzen, Katja

Unternehmenszusammenschlüsse von Supermärkten - eine wettbewerbspolitische Analyse am Beispiel von Edeka und Kaiser's Tengelmann - Erdogan, Yeliz

Zum Potenzial von Kryptowährungen. Eine ökonomische Analyse zu den Chancen und Risiken digitaler Währungen - Perampalam, Abirame

Mergers on digital markets - An economic analysis - Nassar, Hamza

Differenz in der fachschulischen Ausbildung frühpädagogischer Fachkräfte - Kuhn, Mealnie; Landhäußer, Sandra (Heterogenität in Bildung und Differenz in Kindheits- und Sozialpädagogik)
Heterogenität und Differenz sind zentrale und etablierte Begriffe und Konzepte in erziehungswissenschaftlichen Diskursen. Wenngleich diese zum Teil sehr unterschiedlich genutzt werden, sind damit stets Thematisierungsweisen von Unterschieden und Unterscheidungen in pädagogischen Kontexten angesprochen. Dies greift der Band auf und thematisiert verschiedene Zugänge zu Heterogenität und Differenz sowie die damit in Verbindung stehenden Differenzkategorien, Begriffe und Konzepte in kindheits- und sozialpädagogischen Zusammenhängen. Neben theoretischen Beiträgen werden in empirischen Analysen verschiedene Aspekte des Heterogenitäts- und Differenzdiskurses in der Kindheits- und Sozialpädagogik beleuchtet und diskutiert.
Keywords: Sozialpädagogik; frühpädagogischer Fachkräfte; frühpädagogischer Fachkräfte

Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Grade 6 Students’ Perception and Use of Data-Based Decision Trees - Podworny, Susanne; Fleischer, Yannik; Hüsing, Sven (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
Decision-making processes are often based on data and data-driven machine learning methods in different areas such as recommender systems, medicine, criminalistics, etc. Well-informed citizens need at least a minimal understanding and critical reflection of corresponding data-driven machine learning methods. Decision trees are a method that can foster a preformal understanding of machine learning. We developed an exploratory teaching unit introducing decision trees in grade 6 along the question “How can Artificial Intelligence help us decide whether food is rather recommendable or not?” Students’ performances in an assessment task and self-assessment show that young learners can use a decision tree to classify new items and that they found the corresponding teaching unit informative.

Aktuelle Entwicklungen in der Lehrer:innenbildung für Inklusion: Herausforderungen – Konzepte – Perspektiven. Keynote an der Tagung: Lehrer:innenbildung für Inklusion – Hochschuldidaktische Konzepte und Perspektiven an der Pädagogischen Hochschule Heidelberg - Büker, Petra
September 2022

Als Sozialforscher*innen die eigene Schule evaluieren und mitgestalten: Kindersichten auf ein partizipatives Setting in der Grundschule - Büker, Petra; Hüpping, Birgit (Mitbestimmung von Kindern. Grundlagen für Unterricht, Schule und Hochschule)

Reflexion und Reflexivität im Kontext Grundschule. Perspektiven für Forschung, Lehrer:innenbildung und Praxis

Catalytic Properties of High Nitrogen Content Carbonaceous Materials - Lepre, Enrico; Rat, Sylvain; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus; Antonietti, Markus; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Efficient ethanol electro-reforming on bimetallic anodes supported on adenine-based noble carbons: hydrogen production and value-added chemicals - Rodríguez-Gómez, Alberto; Lepre, Enrico; Dorado, Fernando; Sanchez-Silva, Luz; Lopez Salas, Nieves; de la Osa, Ana Raquel (Materials Today Energy)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Materials Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Constructing Interfacial Boron‐Nitrogen Moieties in Turbostratic Carbon for Electrochemical Hydrogen Peroxide Production - Tian, Zhihong; Zhang, Qingran; Thomsen, Lars; Gao, Nana; Pan, Jian; Daiyan, Rahman; Yun, Jimmy; Brandt, Jessica; Lopez Salas, Nieves; Lai, Feili; Li, Qiuye; Liu, Tianxi; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Overcoming Electron Transfer Efficiency Bottlenecks for Hydrogen Production in Highly Crystalline Carbon Nitride‐Based Materials - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Lopez Salas, Nieves; Savateev, Aleksandr; Antonietti, Markus (Advanced Sustainable Systems)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; Lopez Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

“We Are Here!” Oxygen Functional Groups in Carbons for Electrochemical Applications - Jerigová, Mária; Odziomek, Mateusz; Lopez Salas, Nieves (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

Der Studiengang der integrierten Sonderpädagogik an der Universität Bielefeld - Kottmann, Brigitte; Miller, Susanne (Wege der Kooperation im Kontext inklusiver Bildung)
Zur Bewältigung zunehmender schulischer Inklusionsprozesse gilt (multi-)professionelle Kooperation in inklusiven Schulen als ein zentraler Faktor. Die aktuelle Studienlage zeigt, dass die schulische Kooperation weiterhin auszubauen und zu professionalisieren ist. Dieser Sammelband greift aktuelle Fragen hinsichtlich der multiprofessionellen Kooperation sowie der Professionalisierung für Kooperation im Kontext inklusiver Bildung auf. Es werden theoretische Konzepte, empirische Befunde, Praxiseinblicke sowie Professionalisierungsmöglichkeiten für schulische Akteur:innen präsentiert.

Der Übergang von der Grundschule zur weiterführenden Schule als (Soll-)Bruchstelle des Gemeinsamen Lernens? - Kottmann, Brigitte (Grenzen.Gänge.Zwischen.Welten. Kontroversen - Entwicklungen – Perspektiven der Inklusionsforschung)

Inklusion, (k)eine ganz besondere Kunst?! Das Konstrukt "Sonderpädagogische Förderbedarf" (als eine Diagnose) zwischen Schutz und Stigma - Kottmann, Brigitte ("Die Bildung Aller" - Kunstpädagogik und Inklusion)

Rezension des Buches "Schulentwicklung Inklusion. Empirische Einzelfallstudie eines Schulentwicklungsprozesses" von Angelika Bengel - Kottmann, Brigitte (Zeitschrift für Grundschulforschung)

Inklusive Diagnostik in der Schule - Dexel, Timo; Kottmann, Brigitte (Individuelle Förderung - Heterogenität und Handlungsperspektiven in der Schule)

Improper signaling for multicell MIMO RIS-assisted broadcast channels with I/Q imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J (IEEE Transactions on Green Communications and Networking)

A GLRT for estimating the number of correlated components in sample-poor mCCA - Hasija, Tanuj; Marrinan, Timothy (Proc. 30th European Signal Processing Conference (EUSIPCO))

Computational Essays as an Approach for Reproducible Data Analysis in lower Secondary School - Hüsing, Sven; Podworny, Susanne (Proceedings of the IASE 2021 Satellite Conference)
Data Science has become an increasingly important aspect of our everyday lives as we gain a lot of different insights from data analyses, for example in the context of environmental issues. In order to make the process of data analyses comprehensible for lower secondary school students, we developed a data analysis project for computer science classes, focusing on gaining insights from environmental data by using the concept of epistemic programming. In this article, we report on the second implementation of this project, which was conducted in a ninth-grade computer science class. Concretely, we want to examine, how far the students were able to create computational essays to conduct reproducible data analyses on their own. In this regard, the computational essays created with the help of the professional tool Jupyter Notebooks will be examined in terms of aspects of reproducibility.

Ebenen des Narrativen in Bildimpulsen und Erzähltexten : Eine empirische Studie über Wirkungspotentiale von Bildern auf schriftliche Erzählfähigkeiten in der Grundschule - Drepper, Laura

Liquid flow morphology investigation in structured packings for offshore applications using a novel flow imaging sensor - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.

Die Huixian-Figuren: über materielle und immaterielle Aspekte einer Kunstfälschung - Duschner, Paul (Im-Materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag)

Man darf die Unterhaltung nicht den Feinden der Unterhaltung überlassen. - Schroeter-Wittke, Harald; Kirsner, Inge (Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur)

Gottesdienst feiern - Schroeter-Wittke, Harald (Handbuch Studierendenseelsorge. Gemeinden – Präsenz an der Hochschule – Perspektiven)

Einleitung - Schroeter-Wittke, Harald; Janus, Richard (Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren)

Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur

Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren

Echt jetzt?! Fake und Wirklichkeiten - Schroeter-Wittke, Harald (BRU-Magazin)

Steuerreformen: Investitionsstimulus oder bloß heiße Luft? Wann steuerliche Verlustrückträge der Wirtschaft helfen können - Sureth-Sloane, Caren

Men in skintight pants? Changing body images of masculinity in between contemporary athletic and historically ethnic discourses - Haller, Melanie; Gerlsbeck, Silvia (Carmen Dexl (Ed.): De/Constructing Masculinity?, Palgrave)

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Fatshion - Haller, Melanie; Herrmann, Anja; Jun Kim, Tae; Kindinger, Evangelia; Mackert, Nina; Rose, Lotte; Schorb, Friedrich; Tolasch, Eva; Villa, Paula-Irene (Fat Studies. Ein Glossar, Bielefeld)

Synthesis and characterization of multichromophoric iron(II) complexes as novel photosensitizers - Dierks, Philipp

Automatisierte dezentrale Produktionssteuerung für cyber-physische Produktionssysteme mit digitaler Repräsentation der Beschäftigten - Pöhler, Alexander
In dieser Arbeit wird die Entwicklung einer dezentralen Produktionssteuerung mit digitaler Repräsentation zur Anwendung in cyber-physischen Produktionssystemen (CPPS) beschrieben. Die dezentrale Produktionssteuerung geschieht hierbei selbstorganisiert, da sie die Einlastung und Umplanung von Aufträgen sowie die Koordination zwischen den einzelnen Produktionselementen selbstständig übernimmt. Dies erlaubt die automatisierte Steuerung von CPPS. Dabei spielen die Beschäftigten in dieser Betrachtung eine wesentliche Rolle. Ihre Bedürfnisse und Wünsche werden von dem Steuerungssystem berücksichtigt. Dafür wurde das Konzept der digitalen Repräsentation von Beschäftigten entwickelt. Diese Repräsentation erlaubt den individuellen Eingriff von Beschäftigten bei Entscheidungen von dem Steuerungssystem. Das automatisierte dezentrale Steuerungssystem wurde in einer Laborumgebung, die zu einem CPPS umgebaut wurde, implementiert. Darauf basierend wurde eine zweistufige Validierung durchgeführt. Ein Teil der Validierung findet durch eine reale Umsetzung in einem Labor statt, bei der ein Vergleich zu dem vorher im Labor eingesetzten zentralen Produktionssteuerungssystem gezogen wird. Die zweite Validierung erfolgt mit Hilfe einer Simulationsumgebung. Dabei konnte die Implementierung der Selbstorganisation und eine Steigerung der Liefertreue der dezentralen Produktionssteuerung gegenüber heutzutage üblicherweise eingesetzten Verfahren nachgewiesen werden.

Hoffnung POP: Publizistisch-gestalterische Arbeits- und Lebensmodelle im postdigitalen Zeitalter unter Berücksichtigung der transformierenden Rahmenbedingungen. Drei beobachtend-teilnehmende Fallstudien vor dem Hintergrund einer gemeinsamen Forschungsperspektive. - Jacke, Christoph; Venker, Thomas; Roenneke, Stefanie; Godlewsky, Tanja (~Vibes – The IASPM D-A-CH Series. Volume No. 2: „Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)”.)

Sustainability, Solutionism, and the Problem of Music. Kyle Devine interviewed by Christoph Jacke. - Jacke, Christoph; Devine, Kyle (~Vibes – The IASPM D-A-CH Series. Volume No. 2: „Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)”.)

"Zwischen Hartz IV und Vollverbeamtung verläuft nur eine ganz dünne Grenze". Quo-Vadis Pop-Lehre? Eine journalistische Umfrage unter Lehrenden - Jacke, Christoph; Venker, Thomas (Kaput - Magazin für Insolvenz & Pop)

Situational Development of Low-Code Applications in Manufacturing Companies - Kirchhoff, Jonas; Weidmann, Nils; Sauer, Stefan; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)
Companies show an increasing interest in low-code development platforms to facilitate application development by domain experts without sophisticated software development knowledge. Thus, companies aim for a more efficient development of more effective applications since domain experts as so-called citizen developers are no longer limited by the availability and domain knowledge of trained software developers. Nevertheless, efficiency and effectiveness of application development is traditionally also largely influenced by the use of a suitable software development method. Domain experts are, however, not trained in software development methods. This introduces a risk of domain experts creating unusable applications or exceeding the designated time frame of a project (or both). In this paper, we therefore propose an initial version of a situational software development method which supports domain experts in manufacturing companies during the low-code development of applications. The method can be tailored based on situational factors, considering application requirements, features of the used low-code development platform, and characteristics of the development team. We also present feedback corroborating the usefulness of our method and future extension points based on expert interviews.